The Rationalities of Emotion - Cecilea Mun (Rosenberg & Sellier, 2017)
I argue that emotions are not only rational in-themselves, strictly speaking, but they are also instrumentally rational, epistemically rational, and evaluatively rational. I begin with a discussion of what it means for emotions to be rational or irrational in-themselves, which includes the derivation of a criterion for the ontological rationality of emotions (CORe): For emotion or an emotion there exists some normative standard that is given by what emotion or an emotion is against which our emotional responses can be judged or evaluated in virtue of the fact that our emotions manifest our rationality. I conclude with a brief discussion of the implications of this account.